Use of the Evidence-Based practice Attitude and utilization SurvEy to determine the use of evidence-based practice by chiropractic students. - Fernando, Sergio; Whetten, Andrew; Alcantara, Joel (Journal of Chiropractic Education (Allen Press Publishing Services Inc.), 2025)
To assess the attitudes, skills, training, knowledge, barriers, facilitators and use of evidence-based practice (EBP) by chiropractic students and determine the variables important to perceptions of EBP. We utilized the Evidence-Based practice Attitude and utilization SurvEy (EBASE) to achieve our stated objectives. In addition to descriptive statistics, we utilized a generalized linear model to determine the most highly significant items of the EBASE instrument that contributed towards overall EBP perception. A convenience sample of 163 chiropractic students comprised our study population. The majority of students (74%) were 20–29 years of age and achieved a baccalaureate degree or higher (80%) prior to chiropractic matriculation. The respondents indicated positive overall attitude and support of EBP but felt were inadequately trained in EBP and had poor skills in conducting clinical research and systematic reviews. Indicated barriers to EBP were lack of time and lack of clinical evidence for relevant studies. Access to the internet and databases, and ability to download full manuscripts were facilitators to the use of EBP. Generalized linear modelling identified the following as having a significant effect on overall positive EBP perception: confidence in applying research evidence to clinical practice, a lack of interest in EBP, membership in a professional association, quarter of study at institution, and access to tools to critically appraise existing research. Our use of the EBASE questionnaire identified the attitudes, barriers and facilitators to the uptake of EBP by chiropractic students and those variables that contributed to overall EBP perception.